The celebration is on for Class of 2013 - Uribes, Tom::::::::: (2013)
Commencement 2013 at Fresno State is under way. Students were busying prepping for graduation at the Fresno State Alumni Association cap decorating party on Wednesday at the Smittcamp Alumni House.